2015
DOI: 10.1016/j.foodchem.2015.03.075
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-hydrostatic pressure and pH treatments on the emulsification properties of gum arabic

Abstract: This study investigated the emulsification properties of the native gums and those treated at high pressure (800 MPa) both at their "natural" pH (4.49 and 4.58, respectively) and under "acidic and basic" pH (2.8 and 8.0) conditions. The emulsification behaviour of KLTA gum was found to be superior to that of the GCA gum. High pressure and pH treatment changed the emulsification properties of both gums. The acidic amino acids in gum arabic were shown to play an important role in their emulsification behaviour, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…The consequence is that the whole gum would collapse leading to a reduced surface accessibility. These conformational changes with the pH together with the branching nature of the carbohydrate blocks were also recently reported by Ma, Bell, and Davis [61] to explain the differences in the emulsification properties of A. senegal and seyal gums. From the SPR and QCM-D data, it is possible to calculate the hydration state of adsorbed films.…”
Section: Discussionsupporting
confidence: 81%
“…The consequence is that the whole gum would collapse leading to a reduced surface accessibility. These conformational changes with the pH together with the branching nature of the carbohydrate blocks were also recently reported by Ma, Bell, and Davis [61] to explain the differences in the emulsification properties of A. senegal and seyal gums. From the SPR and QCM-D data, it is possible to calculate the hydration state of adsorbed films.…”
Section: Discussionsupporting
confidence: 81%
“…As previously described by Ma et al (2015), DOM was dispersed (10% w/v) by adding the required amount of sample to deionised water with gentle stirring at room temperature (20 °C). The solutions were further degassed under vacuum to remove any entrapped air bubbles.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Gum arabic (GA), one of the most extensively used exudate gums, is a naturallyoccurring complex polysaccharide with small amount of protein (2%-3%), which displays both emulsifying and emulsion stabilising properties (McClements, 2005;Ma et al, 2015). Therefore, the aim of this study was to determine the chemical composition and examine the emulsification properties of DOM in an oil-in-water emulsion with GA, in order to identify the main chemical components that contribute to the emulsifying property.…”
Section: Introductionmentioning
confidence: 99%
“…HHP can inactivate foodborne pathogens, spoilage bacteria, yeasts, and molds with minimal changes in texture, color, flavor, and nutritional quality, as compared to conventional preservation technologies (Medina-Meza, Barnaba, Villani, & Barbosa-Canovas, 2015;Montiel, Martin-Cabrejas, & Medina, 2015). An advantage of HHP is that it mainly acts on noncovalent bonds, with a limited effect on covalent bonds within biological matter (Ma, Bell, & Davis, 2015;Vazquez-Gutierrez, Hernandez-Carrion, Quiles, Hernando, & Perez-Munuera, 2012), thereby exerting a bactericidal activity while preserving the integrity of the BCs present. Zheng et al (2014) reports that a fermented litchi juice treated with HHP showed an increase in organoleptic and sensorial properties like color, flavor, and overall acceptance.…”
Section: High-hydrostatic Pressurementioning
confidence: 99%